Analisis Pemahaman Dalam Mengubah Soal Cerita Ke Dalam Model Matematika Pada Siswa SMA Sidrap - Rizky Ramadhani Zubaer (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2023)
This study aims to analysis of understanding in changing word problems into mathematical models in class X IPA 1 UPT SMA Negeri 6 Sidrap. This type of research is descriptive qualitative. The experimental respondents in this study were 29 students of class X IPA 1 as many as 29 students. Collecting data using research instruments in the form of test sheets and interview guide sheets. Data collection techniques using test techniques and interview techniques. The data analysis technique was carried out with the stages of data reduction, data presentation, and drawing conclusions. The results show that of the three indicators of students' mathematical understanding, it can be seen that the one with the highest percentage is the interpretation understanding indicator with a percentage of 41%, those who master the translation understanding indicator have a percentage of 28%, and those who master the extrapolation understanding indicator have a percentage of 31%. The mathematical understanding that is most mastered by students is the indicator of understanding interpretation, only a few students are able to write indicators of understanding translation and indicators of understanding extrapolation.